The Impact of Trade Liberalization Policies and FDI on Gender Inequalities : A Literature Review - Aguayo‐Tellez, Ernesto (World Bank, 2012)
The Heckscher-Ohlin model predicts that when different economies open to trade, unskilled wages should increase in less skilled labor abundant economies but decrease in skilled labor abundant economies. Trade liberalization policies were expected to reduce wage inequality in developing countries, although affecting negatively the wage structure of the developed countries. However, after three decades of empiric evidence, a large body of literature on the impact of Trade Liberalization Policies (TLP) and Foreign Direct Investment (FDI) on wage inequality and employment have found something different. TLP and FDI have increased wage inequality in both developed and developing countries.